Rapid antiretroviral therapy initiation and its effect on treatment response in MSM in West Africa. (1st November 2021) - Dah, Ter Tiero Elias; Yaya, Issifou; Mensah, Ephrem; Coulibaly, Alou; Kouamé, Jean-Baptiste Malan; Traoré, Issa; Mora, Marion; Palvadeau, Paméla; Anoma, Camille; Keita, Bintou Dembélé; Spire, Bruno; Laurent, Christian
Abstract : Objective: To assess the time from HIV diagnosis to ART initiation and the effect of rapid ART initiation (i.e. within 7 days of HIV diagnosis) on attrition and virologic and immunologic responses among MSM in Burkina Faso, Côte d'Ivoire, Mali, and Togo. Design: Prospective cohort study between 2015 and 2019. Methods: MSM aged 18 years or older newly diagnosed with HIV infection were eligible to participate. ART was proposed to participants upon HIV diagnosis, irrespective of clinical stage and CD4 + cell count, and was initiated as soon as possible, with no specific time frame. Determinants of rapid ART initiation and its effect on treatment outcomes were assessed using multivariate analyses. Results: Of 350 MSM, 335 (95.7%) initiated ART after a median time of 5 days. Of the latter, 216 (64.5%) had rapid ART initiation. The 335 participants were followed up for a median time of 24.1 months. One hundred and eleven (33.1%) were not retained in care. Rapid ART initiation was less likely in participants with a CD4 + cell count at least 200 cells/μl [adjusted odds ratio (aOR) 0.37, 95% confidence interval (CI) 0.15–0.88]. It improved viral load suppression (aOR 6.96, 95% CI 1.98–24.46) but had no effect on attrition (aOR 0.87, 95% CI 0.57–1.33) or CD4 + cell count increase (adjusted coefficient 28.23, 95% CI −17.00 to 73.45). Conclusion: These results in MSM in West Africa support the WHO recommendation for rapid ART initiation. Clinics need to develop context-specific strategies for rapid ART initiation and for retaining MSM in HIV care. ClinicalTrials.gov, number NCT02626286.